Odpowiedzi

Najlepsza Odpowiedź!
2010-02-08T16:10:17+01:00
A) 3(x²-2x+3)-2(x²-5x-1) dla x=2
= 3x²-6x+9-2x²+10x+2=
= x²+4x+ 11

x²+4x+ 11 dla x=2
2²+4*2+ 11
4+8+11 = 23

b) a(2ab +b)-b(a-2ab+a²) dla a=0,1 b=-10
2a²b+ab-ba+2ab²-a²b=
= a²b+2ab²

a²b+2ab² dla a=0,1 b=-10
=0,1²*(-10)+2* 0,1 *(-10)²=
=0,01*(-10) +0,02* 100=
=-0,1+2 = 1,9
2010-02-08T16:16:57+01:00
A)3(x²-2x+3)-2(x²-5x-1)
3x²-6x+9-2x²+10x+2
x²+4x+11
2²+4*2+11
4+8+11=23


b)a(2ab +b)-b(a-2ab+a²)
2a²b+ab-ab+2ab²-a²b
a²b+2ab²
(0,1)²*(-10)+2*0,1*(-10)
0,1+(-2)
0,1-2=-1,9